Peer Effects in Program Participation - Dahl, Gordon B.; Løken, Katrine V.; Mogstad, Magne (SSRN Electronic Journal, 2014)
We estimate peer effects in paid paternity leave in Norway using a regression discontinuity design. Coworkers and brothers are 11 and 15 percentage points, respectively, more likely to take paternity leave if their peer was exogenously induced to take up leave. The most likely mechanism is information transmission, including increased knowledge of how an employer will react. The estimated peer effect snowballs over time, as the first peer interacts with a second peer, the second peer with a third, and so on. This leads to long-run participation rates which are substantially higher than would otherwise be expected.